Time Frequency and Co-movements between Global Economic Policy Uncertainty, Precious Metals and Agricultural Prices: A Wavelet Coherence Analysis and Bootstrap Rolling Window Granger Causality - Abed, Riadh El; Hamouda, Abderrazek Ben (International Journal of Energy Economics and Policy, 2024)
Examining the links between economic uncertainty and precious metals allows us to explore the interconnectedness of various economic factors and their potential impact on markets, investments, and global trade. Precious metals such as gold and silver have historically been used as safe havens during times of economic uncertainty. Understanding how these metals interact with fluctuating economic policies can help assess their role as a safe haven and their importance to investors. Analyzing the links between precious metals, economic uncertainty, and agricultural prices can help policymakers design measures to mitigate negative impacts on the economy and foster financial and food stability. The main objective of this paper is to examine the co-movements between global economic policy uncertainty and each commodity such as oil, precious metals and agricultural prices. We employ two empirical approaches such as wavelet coherence and bootstrap rolling window Granger causality. The dynamic causality according to the bivariate framework between variables is analyzed. We used monthly data during the period span from January 2004 to September 2022. Empirical results indicate the evidence of unidirectional, bidirectional and absence of causality between variables. In addition the co-movements between GEPU and each variable are positive and negative.